PENGARUH BAKTERI ENDOFIT ASAL POHON BERHABITAT BASAH TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS PADI SAWAH (Oryza sativa) - Mutia Nawawi; Johan Matinahoru; Miranda Hadijah (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study focused on the effect of endophytic bacteria from trees with wet habitats on the growth and productivity of lowland rice (Oryza sativa). Endophytic bacteria were obtained from root extracts of three plant species, namely kayu burung (bird's wood), forest catangensis (katapang hutan), and kayu marsegu (marsegu wood). Samples of the roots of kayu burung (bird's wood) and kayu burung (bird's wood) were collected from Ambon Island, while the roots of katapang hutan and kayu burung (bird's wood) came from Seram Island. The study used a descriptive method with field observations. Parameters observed included plant height, number of leaves, and dry grain weight per stem. The results showed that the highest average plant height was obtained in the treatment of endophytic bacteria from kayu burung (14.16 cm), followed by kayu marsegu (12.16 cm) and katapang hutan (10.16 cm). The treatment of endophytic bacteria containing Monococcus, Streptococcus, and Staphylococcus had a positive effect on vegetative growth and rice production. Endophytic bacteria from marsegu wood and forest catangensis produced the highest dry grain weight, namely 1.216 g per stem. These results demonstrate the potential of endophytic bacteria from forest plants as biological agents to increase rice productivity in lowland rice.